Praktik Jual Beli Online Shope Pada PT. Shoppe Indonesia dalam Prespektif Hukum Perlindungan Konsumen di Indonesia - meirza aulia chairani (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2021)
Abstract - The current buying and selling practice in Indonesia is very high, by using a mobile phone, one click the goods will be sent home easily. The famous online buying and selling application or online advertising, one of which is the online shop buying and selling application. Various kinds of products provided by consumers can choose what items to buy. However, sometimes the order that we buy doesn't match what we ordered. This results in losses for consumers. Lack of consumer protection in online buying and selling in Indonesia due to a lack of regulations that protect consumers, business actors, online application parties, carriers, and related parties. Therefore, this research uses an empirical juridical method, with a statutory approach and a conceptual approach.Â Keyword: consumer protection, e-commerce, buy and sell